SISTEM INFORMASI PENGELOLAAN INVENTARIS UMKM BERBASIS WEB DENGAN PENDEKATAN AGILE - Minasa, Sunggu; Sya'bandyah, Fitri; Abdul Muhaemin, Muhamad Nurdin; Juliandani, Bayu (Universitas Sangga Buana, 2024)
A web-based inventory management information system for MSMEs with an Agile methodology approach was developed to overcome the main challenges faced by MSMEs, especially related to limited resources. The system is designed to provide real-time data access, which supports faster and more accurate decision-making. With the Agile approach, system development is iterative, allowing for adjustments to evolving needs and direct feedback from users. The results showed that the implementation of this system successfully improved operational efficiency, inventory management capabilities, and customer satisfaction. The integration of advanced information technology, along with effective project management, enables MSMEs to better respond to changes and strengthen competitiveness. This research makes a significant contribution to the development of innovative information systems that support the growth and sustainability of MSMEs.